PERLINDUNGAN HUKUM BAGI PENERIMA WARALABA TERHADAP PERUBAHAN PRODUK SECARA SEPIHAK. - Saputro, Wahyu Hidayat; Kadir, Taqiyuddin; Kumala, Yudha Cahya (LPPM Institut Pendidikan Nusantara Global, 2024)
The development of the business world penetrates the boundaries of space, time and territory of a country. One of the breakthroughs made by business people is business development through a franchise system, which in Indonesia is termed a franchise. Republic of Indonesia government regulation no. 42 of 2007 concerning franchising provides a definition of a franchise as a special right owned by an individual or business entity to a business system with business characteristics in order to market goods and/or services that have been proven successful and can be utilized or used by other parties based on a franchise agreement. In Indonesia, the legal regulations regarding franchising are not yet complete, considering that regulation through law has not been touched by the government. This is necessary to prevent franchise business actors from unwanted losses due to the incomplete legal instruments that protect them. This research raises the issue of what are the legal consequences of franchise agreements in the event of unilateral changes to franchise products by the franchisor and what is the legal protection for franchisees? for unilateral changes to franchise products by the franchisor. By using two legal theories as analysis tools, namely the legal protection theory from Satjipto Rahardjo and the legal consequences theory from Soeroso. The method used in this research is a normative juridical research method, namely legal research carried out by examining library materials or secondary data only. The research approaches used are a statutory approach, a case approach, a conceptual approach, an analytical approach and techniques for collecting legal materials by identifying and inventorying positive legal materials, literature. books, journals and other source materials, the technique for analyzing legal materials is carried out using legal interpretation (interpretation), systematic interpretation and methods of analogous legal construction, legal refinement construction (rechtsverfijning) and a contrary argument. The legal consequences of a franchise agreement in the event of a unilateral change to the franchise product by the franchisor, is the disappearance of the legal situation and relationship between the franchiser and the franchisee due to the franchiser's default which has implications for the franchisee experiencing losses due to not providing products, tools and materials for the franchise object. as is the classification that has been agreed. Legal protection for franchisees for unilateral changes to franchise products by the franchisor will be better protected if the Franchise Agreement regulates specific protection of the suitability of the franchise object, and the franchise agreement is not made standardly by the franchisor but is formulated together with the franchisee. . Because standard agreements are more susceptible to taking sides for the unilateral benefit of the agreement maker.